PFOA, PFOS and PFHxS toxicokinetic considerations for the development of an in vivo approach for assessing PFAS relative bioavailability in soil - Albert L. Juhasz; Farzana Kastury; Ruby Jones; Mahima Seeborun; Tanya Caceres; Carina Herde; Michelle Cavallaro; Sarah Dilmetz; Joshua Hutchings; Yevgeniya Grebneva; Chris Desire; Peter Hoffmann (Environment International)
A Sprague-Dawley rat model was utilized to elucidate perfluorooctanoic acid (PFOA), perfluorooctanesulfonic acid (PFOS) and perfluorohexanesulfonic acid (PFHxS) toxicokinetics with a goal of developing an in vivo approach for quantifying PFAS relative bioavailability in impacted soil. Following single dose administration (gavage) of ∼ 0.2–2000 µg kg−1 BW of PFOA, PFOS or PFHxS, differences in PFAS blood, organ and excreta concentrations were observed over 120 h although linear dose responses were determined for area under the blood plasma time curves (AUC; PFOA, PFHxS), liver accumulation (LA: PFOS) and urinary excretion (UE; PFOA, PFHxS). Oral and intravenous dose (∼20 µg kg−1 body weight) comparisons highlighted the high absolute bioavailability of PFOA (AUC: 100.3 ± 23.4 %; UE: 94.7 ± 26.6 %), PFOS (LA: 102.9 ± 15.6 %) and PFHxS (AUC: 88.3 ± 15.1 %; UE: 90.9 ± 7.3 %). Two spiked (14C-PFOA: 4360 ± 218 µg kg−1) and two PFAS impacted soils (PFOS: 1880–2250 µg kg−1; PFHxS: 61.2–65.5 µg kg−1) were utilized to measure PFAS relative bioavailability in soil matrices. In all soils, PFAS relative bioavailability was > 86 % (PFOA: 87.0–90.9 %; PFOS: 86.1–90.4 %; PFHxS: 86.5–97.0 %) although the method could quantify bioavailability reductions (25.6–88.9 %) when hydrophobic and electrostatic interactions were enhanced through the addition of carbon-based amendments (5–10 % w/w).